Resistance of House Fly, Musca domestica L. (Diptera: Muscidae), to Five Insecticides in Zhejiang Province, China: The Situation in 2017. (23rd June 2019) - Wang, Jin-Na; Hou, Juan; Wu, Yu-Yan; Guo, Song; Liu, Qin-Mei; Li, Tian-Qi; Gong, Zhen-Yu
Abstract : Objectives . High dependency on pesticides could cause selection pressure leading to the development of resistance. This study was conducted to assess the resistance of the house fly, Musca domestica, to five insecticides, namely, permethrin, deltamethrin, beta-cypermethrin, propoxur, and dichlorvos, in Zhejiang Province. Methods . Field strains of house flies were collected from the 12 administrative districts in Zhejiang Province in 2011, 2014, and 2017, respectively. Topical application method was adopted for the bioassays. The probit analysis was used to determine the median lethal doses with the 95% confidence interval, and then the resistance ratio (RR) was calculated. The insecticides resistance in different years and the correlations of the resistance between different insecticides were also analyzed. Results . The resistance of field strains house flies to insecticides in Zhejiang Province was relatively common, especially for permethrin, deltamethrin, and beta-cypermethrin. The reversion of the resistance to dichlorvos was found, and most of the field strains in Zhejiang Province became sensitive to dichlorvos in 2017. Propoxur was much easier to cause very high level of resistance; the Hangzhou strain had the highest RR value more than 1000 in 2014, and five field strains had the RR value more than 100 in 2017. Compared to 2011 and 2014, the resistance of the house flies to propoxur and deltamethrin increased significantly in 2017. The resistance of permethrin, deltamethrin, beta-cypermethrin, and propoxur was significantly correlated with each other, and the resistance of dichlorvos was significantly correlated with beta-cypermethrin. Conclusions . Our results suggested that resistance was existed in permethrin, deltamethrin, beta-cypermethrin, and propoxur in the house flies of Zhejiang Province, while the resistance reversion to dichlorvos was found.